Mesenchymal Stem Cell Therapy Overcomes Steroid Resistance in Severe Gastrointestinal Acute Graft-Versus-Host Disease. (21st May 2019) - Moritani, Kyoko; Miyawaki, Reiji; Tokuda, Kiriko; Ochi, Fumihiro; Eguchi-Ishimae, Minenori; Tauchi, Hisamichi; Eguchi, Mariko; Ishii, Eiichi; Nagai, Kozo
Abstract : The authors describe the high effectiveness of human mesenchymal stem cell (hMSC) therapy to treat steroid-refractory gastrointestinal acute graft-versus-host Disease (aGVHD) in a 15-year-old boy with acute lymphoblastic leukemia (ALL). He received allogeneic hematopoietic stem cell transplantation due to high-risk hypodiploid ALL. Around the time of engraftment, he developed severe diarrhea following high-grade fever and erythema. Although methylprednisolone pulse therapy was added to tacrolimus and mycophenolate mofetil, diarrhea progressed up to 5000 6000 ml/day and brought about hypocalcemia, hypoalbuminemia, and edema. Daily fresh frozen plasma (FFP), albumin, and calcium replacements were required to maintain blood circulation. After aGVHD was confirmed by colonoscopic biopsy, MSC therapy was administered. The patient received 8 biweekly intravenous infusions of 2×10 6 hMSCs/kg for 4 weeks, after which additional 4 weekly infusions were performed. A few weeks after initiation, diarrhea gradually resolved, and at the eighth dose of hMSC, lab data improved without replacements. MSC therapy successfully treated steroid-refractory gastrointestinal GVHD without complications. Despite life-threatening diarrhea, the regeneration potential of children and adolescents undergoing SMC therapy successfully supports restoration of gastrointestinal damage. Even with its high treatment costs, SMC therapy should be proactively considered in cases where young patients suffer from severe gastrointestinal GVHD.